Gold (Au), Silver (Ag) and Bimetallic Au/Ag Core-Shell Nanoparticles: Synthesis and Applications in 4-Nitrophenol Reduction Reactions - Nurjannah Nurjannah; Bualkar Abdullah; Yuliati Herbani (Molekul, 2022)
Au, Ag, and Au/Ag core-shell nanoparticles (NPs) were synthesized in aqueous solution by chemical reduction. UV-Vis absorption spectra confirmed a single surface plasmon resonance (SPR) peak for Au and Ag NPs, at 520 nm and 419 nm, respectively. Au/Ag core-shell NPs' UV-Vis spectra showed two distinct peaks at 385 and 480 nm, confirming a core-shell structure different from its alloy counterpart. Transmission electron microscopy (TEM) shows a relatively uniform spherical shape for both Au and core-shell Au/Ag NPs, while Ag NPs have a variety of forms such as a prism, rod, and spherical. The average size of the synthesized nanoparticles was quite similar, between 18 and 25 nm. The 4-nitrophenol reduction reaction model was used to study the catalytic ability of nanoparticles where Au/Ag core-shell NPs showed higher catalytic activity than the other monometallic NPs used in this study.